2018
DOI: 10.1177/1062860618768069
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Rounds Improve Timing of Appropriate Palliative Care Consultation on a Hospitalist Service

Abstract: Despite known benefits, palliative care (PC) consultation for hospitalized patients remains underutilized. The objective was to improve frequency and timeliness of appropriate inpatient PC consultation. On 2 of 11 hospitalist teams, a PC representative attended discharge rounds twice a week. Control teams' discharge rounds were unenhanced. Subjects were all patients admitted to a hospitalist service in a quaternary academic medical center. The primary outcome was change in provision of PC consultation over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Here, improvements have been shown when specialist PC was integrated into existing practice through interdisciplinary teamwork, 24 , 26 palliative consultations 4 , 24 and palliative rounds. 27 Since palliative medicine recently has become a formal speciality in Sweden, a model for cooperation between specialized palliative medicine and other specialties is of importance as has been emphasized in other countries in the corresponding situation. 28 Educational activities including not only health care students and professionals but also patients, families and the public are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Here, improvements have been shown when specialist PC was integrated into existing practice through interdisciplinary teamwork, 24 , 26 palliative consultations 4 , 24 and palliative rounds. 27 Since palliative medicine recently has become a formal speciality in Sweden, a model for cooperation between specialized palliative medicine and other specialties is of importance as has been emphasized in other countries in the corresponding situation. 28 Educational activities including not only health care students and professionals but also patients, families and the public are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, we found that whether a patient was cared for by a medical service or a surgical service affected their receipt of PCC with regard to the primary language they spoke: The finding of low utilization of PCC has been consistently reported in the literature. 3,18,23,24 However, it remains unclear whether there is a disproportionate underutilization of PCC in racial and ethnic minorities. Our findings of there being no association between a patient's race/ethnicity and their receipt of PCC at our hospital is consistent with those reported for patients with devastating neurovascular events 11,25 and terminal cancer, 9,10 but in sharp contrast to those reported for patients with renal disease 4 and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, there is still underutilization of these services in the inpatient setting. 3 A review of patient-level factors associated with low utilization of PCC in the inpatient setting suggests that race and ethnicity are possible contributors, while variables such as education level, English language proficiency, insurance status, and income remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…9 There is a growing need for hospital medicine physicians to access palliative care for their patients. [10][11][12] However, hospital-based palliative care resources are too limited to ensure that these patients receive palliative care. 13 Therefore, to meet the palliative care needs of these seriously ill patients at Mount Sinai Hospital, a 1144-bed quaternary-care teaching facility located in New York City, we initiated an innovative social worker-led primary palliative care model embedded within the hospital medicine service (Fig.…”
Section: Introductionmentioning
confidence: 99%